ChemInform Abstract: Efficient and General Aerobic Oxidative Cross‐Coupling of THIQs with Organozinc Reagents Catalyzed by CuCl2: Proof of a Radical Intermediate. Issue 2 (23rd December 2015) - Wang, Tongtong; Schrempp, Michael; Berndhaeuser, Andreas; Schiemann, Olav; Menche, Dirk
Abstract: A new and general method for the concise C‐1 alkylation of tetrahydroisoquinolines is described.